Generalized arterial calcification of infancy – Fetal diagnosis to postnatal management - Lamk Kadiyani; PM Shivaprasad; Sivasubramanian Ramakrishnan; Anubhuti Rana; Niraj Pandey (Annals of Pediatric Cardiology)
Generalized arterial calcification of infancy is a rare entity with poor fetal and postnatal outcomes and high morbidity in survivors. Half of the cases are diagnosed intrauterine due to hemodynamic compromise, and the associated manifestations pose unique management challenges. We hereby report an account of a fetal diagnosis in a referral for hydrops with postnatal evaluation and management.